23.9k views
5 votes
(t9)-8 what is the simplify expression

User Origineil
by
5.3k points

2 Answers

6 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ (t^9)^(-8)\implies t^(-8\cdot 9)\implies t^(-72)\implies \cfrac{1}{t^(72)}

User David Yang Liu
by
5.8k points
1 vote
The answer would be -72t because all you would have to do is multiply the expression
User Sudipto Mukherjee
by
5.9k points